Elastic-plastic analysis of the adhesively bonded end-notched flexure specimen. (1st February 2018) - de Morais, A.B.
Highlights: A beam model was developed for metal adhesively bonded ENF specimens. Expressions were obtained for the effective crack length data reduction scheme. A cohesive zone was considered through adhesive elastic-perfectly plasticity. The model provided a closed-form expression for the plastic zone size. The effect of the plastic zone size on fracture energy measurements was analysed. Abstract: The end-notched flexure (ENF) specimen has often been employed to characterise the mode II fracture of adhesive joints. This paper reports a beam model for ENF specimens with metal adherends and typical bondline thickness values. The initial formulation adopting adhesive linear elasticity predicted accurately the shear stress distribution, the compliance and the strain-energy release rate. The adhesive elastic-perfectly plastic behaviour subsequently introduced generated a plastic zone whose size could be predicted by a closed-form expression. The model provides a basis for selecting specimen geometries that enable accurate fracture energy measurements from a corrected beam theory with effective crack length scheme.